Who has been affected, how and why? The spillover of the global financial crisis to Sub-Saharan Africa and ways to recovery - Sophie Chauvin; André Geis (European Central Bank (ECB), 2011)
This paper first presents a comprehensive analysis of the significance of different transmission channels of the global economic and financial crisis to Sub-Saharan African countries. It then examines the repercussions of the crisis for the growth of gross domestic product (GDP) and its components; this is complemented by a study of the responses of monetary and fiscal authorities to the challenges posed by the crisis, both in regional terms and on the basis of selected country case studies. Finally, the paper highlights medium-term to long-term challenges for ensuring a sustainable recovery and for fostering resilience against potential future shocks.The authors find that the intensity of the impact of the crisis varies widely across countries, with a lack of export diversification apparently having been particularly conducive to its transmission. However, the analysis of the magnitude of the observed swings in macroeconomic variables also reveals that although they were large, they were not exceptional and are comparable to fl uctuations Sub-Saharan Africa has witnessed in the recent past. Furthermore, in a non-negligible number of instances the extent of the slowdown seems to have been determined by domestic factors as well. Particularly, policies and conditions prior to the global recession, rather than crisis contagion per se, appear decisively to have shaped the scope of possible responses in many cases.As a result, many of the policy lessons Sub- Saharan Africa might draw from the crisis do not involve radical deviation from the policies in place before. Efforts to improve the management of resource revenue for commodity-dependent countries, necessary reforms of the economic and business environment to enable a diversification of the export base, and further regional integration might help to alleviate possible future external shocks. Additionally, the crisis re-emphasises the need to back growth prospects by redefining sectoral priorities.
Keywords: E52; E31; D84; 330; balance of payments; Global economic crisis; intern. spillover; Regional growth; Sub-Saharan Africa